KALIMAT TANYA DALAM BAHASA INGGRIS DAN BAHASA TOMBULU (SUATU ANALISIS KONTRASTIF) - Ellyezar Mangimbulur; Donald R. Lotulung; Theresia M.C Lasut (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2022)
Â  Â  Â  Â  KALIMAT TANYA DALAM BAHASA INGGRIS DAN BAHASA TOMBULUÂ  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  (SUATU ANALISIS KONTRASTIF)Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â Ellyezar Mangimbulur1Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â Donald R. Lotulung2Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â Theresia M. C. Lasut3Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â ABSTRACTÂ  Â  Â This research is entitled â€œInterrogative Sentences in English and Tombulu Language (A Contrastive Analysis)â€. This research is an attempt to analyze, describe and contrast English and Tombulu language which focuses on the interrogative sentences in relation to their forms and functions in both languages. The theories used in this research are Aarts (2001) theory to find out forms and functions of interrogative sentence and Ladoâ€™s (1957) theory to contrast and analyze the interrogative sentences in English and Tombulu language to find out the differences and similarities between both languages. The data of English language were collected from two books entitled English Syntax and Argumentation and English Syntactic Structures, whereas the data of Tombulu language were taken from four native speakers as informants who were born and live in Pinaras, North Sulawesi. The results of this study show that English and Tombulu language have differences as well as similarities. There are three similarities and seven differences between both languages. English and Tombulu language have similarities in the form of interrogative sentences, namely yes/no interrogatives, wh-interrogatives, alternative interrogatives and rhetorical question. English and Tombulu language have the same question word, which is in front of the sentence. Both languages also have the same function of question word. English and Tombulu language have different forms of yes/no interrogatives. English has a tag-question while Tombulu does not. The difference in the number of question word in the two languages, English language has eight while Tombulu only has six forms of question word. English has its own question words for the subject and object, while Tombulu language only has one question word for both. Tombulu language has its own question word to ask about numbers, while English does not. However, in English there is question word to ask a polite question.Keywords: Interrogative Sentence, English, Tombulu Language, Contrastive Analysis1 Mahasiswa yang bersangkutan2 Dosen Pembimbing Materi3 Dosen Pembimbing Teknik